(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
There are increasing numbers of people infected with sexually transmitted infections, adolescents who begin their sexual practices earlier, teenage births that involve biological risks and the consequent disorders in several areas. People with intellectual disabilities do not escape from this problem, being the most vulnerable population to be at risk. In view of this, it has been decided to carry out a research with students of an I. E., who have intellectual disabilities to implement with them a software with contents of sexual and reproductive education, analyzing the before and after the application of the software. The results show that the software is a tool that contributes to the teaching-learning of this topic, by providing them with updated information and correct terminology. Therefore, it is concluded that it is a transforming educational proposal, which favors the construction of social skills, the basis for life in the community.